The Development of Global Higher Education in a World of Transformation (Journal of Education and Development, 2018)
Globalization has forced higher education into a new world, a world of change, instability and ambiguity, shaped by an increasingly integrated world economy, technology, an international knowledge network, and other forces beyond the control of higher education institutions. Futurists predict that the education systems of tomorrow will be drastically different from those of today. They forecast innovative approaches to teaching and learning will proliferate and will be used more effectively because of technology and telecommunications. Traditional universities historically have been producers of knowledge in the form of human capital, research, and scholarship and are now challenged to tap into the expanding need for lifelong learning. The need and desire for higher education are growing, but higher education is challenged to make significant changes driven by globalization and technology.